2007
DOI: 10.1080/14616730601151417
|View full text |Cite
|
Sign up to set email alerts
|

A controlled study of Hostile-Helpless states of mind among borderline and dysthymic women

Abstract: The aim of this study was to determine whether women with borderline personality disorder (BPD) are more likely than those with dysthymia to manifest contradictory Hostile-Helpless (HH) states of mind. A reliable rater blind to diagnosis evaluated features of such mental representations in transcripts of Adult Attachment Interviews from 12 women with BPD and 11 women with dysthymia of similar socioeconomic status (SES), all awaiting psychotherapy. In keeping with three hierarchical (non-independent) a priori p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 44 publications
5
47
0
5
Order By: Relevance
“…Barone, 2003;Fonagy et al, 1996), and some called attention to the pivotal role of disorganization in borderline functioning (e.g. Fonagy et al, 1996;Lyons-Ruth et al, 2007). The distribution of BPD attachment in our whole sample was F ¼ 14%; Ds ¼ 51%, E ¼ 35%, U/ CC ¼ 40%, only partially consistent with those previously collected and, most of all, not instrumental, in this form, at better clarifying the quality of insecurity observed.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Barone, 2003;Fonagy et al, 1996), and some called attention to the pivotal role of disorganization in borderline functioning (e.g. Fonagy et al, 1996;Lyons-Ruth et al, 2007). The distribution of BPD attachment in our whole sample was F ¼ 14%; Ds ¼ 51%, E ¼ 35%, U/ CC ¼ 40%, only partially consistent with those previously collected and, most of all, not instrumental, in this form, at better clarifying the quality of insecurity observed.…”
Section: Discussionsupporting
confidence: 80%
“…If one looks only at past AAI studies of individuals with BPD, we find they represent 200 (or 2%) of the 10,000 AAI classifications reviewed by Bakermans-Kranenburg and van IJzendoorn (2009). Ten studies to date have considered the specific links between attachment and BPD utilizing the AAI (Barone, 2003;Barone, Borellini, Madeddu, & Maffei, 2000;Diamond, Stovall-McClough, Clarkin, & Levy, 2003;Fonagy, Leigh, Steele, Steele, Kennedy, Matoon, et al, 1996;Levy, Mehan, Kelly, Reynoso, Weber, Clarkin, et al, 2006;Lyons-Ruth, Melnick, Patrick, & Hobson, 2007;Patrick, Hobson, Castle, Howard, & Maughan, 1994;Rosenstein & Horowitz, 1996;Stalker & Davies, 1995;Stovall-McClough & Cloitre, 2003;van IJzendoorn, Feldbruggen, Derks, de Ruiter, Verhagen, Philipse, et al, 1997). While these studies do have some of the common methodological shortcomings mentioned above (often relying on small samples from in and out-patient sources, and various diagnostic criteria), they share the merit of having used the AAI, a highly reliable assessment method which allows more conclusive inquiry into the developmental issues implied in the disorder.…”
Section: Attachment and Borderline Personality Disordermentioning
confidence: 96%
“…For example, Lyons-Ruth and colleagues (e.g. Lyons-Ruth, 2003;Lyons-Ruth, Melnick, Patrick, & Hobson, 2007;Lyons-Ruth & Spielman, 2004) developed the hostile/helpless (HH) category to explain why some nontraumatized mothers have disorganized children. Mothers who were not judged unresolved nevertheless manifested a pervasive sense of hostility or helplessness throughout the AAI transcript.…”
Section: Introductionmentioning
confidence: 98%
“…Lyons-Ruth, Melnick, Patrick, and Hobson (2007) found that adult BPD patients were significantly more likely than depressed patients to refer to engaging in role-confused forms of behavior toward the parent in childhood. Lyons-Ruth, Choi-Kain, Pechtel, Bertha, and Gunderson (2011) found that borderline patients, compared to controls without BPD, were more likely to report a lack of protection in their relationships with their mothers, and this perceived lack of protection was further predictive of the patient's baseline cortisol elevation in anticipation of a conflict discussion with the mother.…”
Section: Discussionmentioning
confidence: 97%